2002
DOI: 10.1034/j.1600-0765.2002.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of three‐dimensional determination of root surface roughness

Abstract: In comparing and evaluating the instruments that are used in root debridement, roughness constitutes a standard variable that is assessed. The purpose of this study was to describe the conditions and requirements for the three-dimensional roughness measurements of tooth roots using a laser profilometer. Impressions were made of 60 instrumented and 12 untreated root surfaces, which were then measured using a dynamically focussing optical profilometer (Mikrofocus, UBM, Karlsruhe, Germany). To separate roughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 7 publications
(8 reference statements)
1
28
0
1
Order By: Relevance
“…During the damaging process of oil-impregnated insulation paper, the microstructure of the surfaces of the insulation paper in different damaging stages was studied using an atomic force microscope (AFM.IPC-208B), and the three-dimensional roughness was calculated [26,27]. For more efficient representation, the surfaces of the insulation paper were divided into three ring-zones, namely, the internal, medium, and external rings.…”
Section: Discussionmentioning
confidence: 99%
“…During the damaging process of oil-impregnated insulation paper, the microstructure of the surfaces of the insulation paper in different damaging stages was studied using an atomic force microscope (AFM.IPC-208B), and the three-dimensional roughness was calculated [26,27]. For more efficient representation, the surfaces of the insulation paper were divided into three ring-zones, namely, the internal, medium, and external rings.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Busslinger et al [9] reported that a piezoelectric device left a rougher surface than a magnetostrictive device after instrumentation. The roughness of the root surface after a scaling procedure is a factor to consider for maintenance because it has also been reported that bacterial plaque adheres easily to the rough root surfaces after treatment [10,11]. A comparison of different piezoelectric or magnetostrictive ultrasonic devices can be expected to produce differences in tooth surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of the ultrasonic scaler has appeared as an important alternative for daily clinical use due to its several advantages, such as access to furcation, less operator tiredness, pocket penetration and less time required for scaling and root planning (1,2). Studies evaluating differences in the magnitude of root surface alterations produced by hand, sonic, and ultrasonic instruments are inconclusive (1)(2)(3). Considering manual and ultrasonic scalers, some reports indicate that manual scalers remove more root substance (4), whereas others found that ultrasonic scalers do so (2).…”
Section: Introductionmentioning
confidence: 99%
“…The RLTSI evaluates roughness and substance loss concomitantly. However, the loss of tooth substance with the use of a specific instrument cannot be directly correlated with the roughness produced on root surface (3,9), needing a separate evaluation (9).…”
Section: Introductionmentioning
confidence: 99%